Pelatihan Metode Pembelajaran Menyenangkan Berbasis Integrated Joyful Religious Learning - Salahuddin; MS, Uyun Nafiah; Sakunti, Sri Ramdayeni; Safitri, Resdiana; Fikri, Ahmad; M. Yahuda; Hasirah (Lembaga Dongan Dosen, 2023)
Islamic religious education at primary madrasahs plays a pivotal role in moulding the moral and spiritual values of the youth. This article introduces a specialized training program for primary madrasah educators known as the